2008
DOI: 10.1007/s00441-007-0559-3
|View full text |Cite
|
Sign up to set email alerts
|

Doxazosin reduces cell proliferation and increases collagen fibers in rat prostatic lobes

Abstract: We investigated the effects of doxazosin (Dox), an alpha-adrenoceptor antagonist used clinically for the treatment of benign prostatic hyperplasia (BPH), on the rat prostatic complex by assessing structural parameters, collagen fiber content, cell proliferation, and apoptosis. Adult Wistar rats were treated with Dox (25 mg/kg per day), and the ventral (VP), dorsolateral, and anterior prostate (AP) regions of the prostate complex were excised at 3, 7, and 30 days after treatment. At 24 h before being killed, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…Their finding suggests that a1-blockers induce dedifferentiation of smooth muscle into fibroblasts and myofibroblasts, and may thus induce alteration of tissue architecture. More recently, Justulin et al [9] reported that when rats were given repeated doses of doxazosin, they exhibited collagen fiber accumulation in prostatic stroma and reduction in smooth muscle. On the basis of this finding, they suggested the possibility that continued oral treatment with doxazosin would alter prostatic tissue architecture and reduce the efficacy of a1-blockers [9].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Their finding suggests that a1-blockers induce dedifferentiation of smooth muscle into fibroblasts and myofibroblasts, and may thus induce alteration of tissue architecture. More recently, Justulin et al [9] reported that when rats were given repeated doses of doxazosin, they exhibited collagen fiber accumulation in prostatic stroma and reduction in smooth muscle. On the basis of this finding, they suggested the possibility that continued oral treatment with doxazosin would alter prostatic tissue architecture and reduce the efficacy of a1-blockers [9].…”
Section: Discussionmentioning
confidence: 97%
“…More recently, Justulin et al [9] reported that when rats were given repeated doses of doxazosin, they exhibited collagen fiber accumulation in prostatic stroma and reduction in smooth muscle. On the basis of this finding, they suggested the possibility that continued oral treatment with doxazosin would alter prostatic tissue architecture and reduce the efficacy of a1-blockers [9]. These views were endorsed by the findings of our study, in which treatment with a1-blockers resulted in alteration of prostatic tissue architecture.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thirty-day treatment of normal rats with a high dose of doxazosin produced a 20% reduction in prostatic weight and an increase in the density of stromal collagen fibers (Justulin et al 2008). Using the model described above, where BPH was induced in the rat by implantation of fetal urogenital sinus, 21-day treatment with naftopidil, a preferential a 1D -adrenoceptor antagonist, inhibited cellular proliferation in both epithelia and stroma.…”
Section: Effects Of A-adrenoceptor Antagonists On Cellular Proliferationmentioning
confidence: 97%